2020
DOI: 10.12688/f1000research.24123.1
|View full text |Cite
|
Sign up to set email alerts
|

The use of essential oils as a growth promoter for small ruminants: a systematic review and meta-analysis

Abstract: Background: Due to their antimicrobial properties and safety, essential oils are currently proposed as a sustainable option for antibiotic alternatives in the livestock sector. This current systematic review and meta-analysis investigated the effects of dietary essential oil supplements on growth response of small ruminants. Methods: A total of 12 studies (338 small ruminants) were included in this meta-analysis. The overall effect size was quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…The systematic review and meta-analysis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline 12 . A completed PRISMA checklist is available in Reporting guidelines 13 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The systematic review and meta-analysis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline 12 . A completed PRISMA checklist is available in Reporting guidelines 13 .…”
Section: Methodsmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 3. Extracted data of outcome measures is available as Extended data 30 .…”
Section: Publication Bias Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fitobiotik merupakan aditif pakan yang berasal dari tanaman, baik berupa minyak atsiri, herbal maupun oleoresin (Gheisar dan Kim, 2018). Aditif pakan fitobiotik memiliki efek biologis berupa antimikroba, antioksidan dan imunomodulator (Huang dan Lee, 2017;Andri et al, 2018;Andri et al, 2020;). Salah satu kandidat fitobiotik yang dapat digunakan untuk ayam petelur adalah Fitobiotik Ekstrak Daun Jati (FEDJ).…”
Section: Pendahuluanunclassified